Visão futuro: comunidade autogestionável - Cassemiro, Patrícia Ferreira [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Along of the Brazilian territory is to encourage a lot of self-management communities, seeking a new way of social organization through of cultural practices and economic antagonistic logic of the capitalist system. These communities create a lifestyle which we are not used in the context of modern life, they are focused to a greater preservation of nature, to an economy based on spiritualization and cultural exchange. The peculiarity of these communities is to offer the same structure as a modern city, electricity, clothing, basic sanitation, food among others, which the state already offers, but with alternative ways.For a more specific study was selected community-Porangaba Future Vision, São Paulo. Through this case of study, it is thought to enable a better understanding of how it is possible within a country emerge a community that creates its own structure encompassed by cultural practices and economic characteristics and finally understanding what are the effects on the geographic area

Ao longo do território brasileiro está a fomentar diversas comunidades auto-gestoras, que buscam uma nova forma de organização social por meio de práticas culturais e econômicas antagônicas a lógica do sistema capitalista. Essas comunidades criam um estilo de vida da qual não estamos acostumados no contexto da vida moderna, estão voltados para uma maior preservação da natureza, para uma economia baseada na espiritualização e no intercâmbio cultural. A peculiaridade dessas comunidades está em oferecer a mesma estrutura que uma cidade moderna: energia elétrica, vestuário, saneamento básico, alimentação dentre outros, dos quais o Estado já oferece, entretanto com meios alternativos.Para um estudo mais específico foi selecionada a comunidade Visão Futuro- Porangaba, interior de São Paulo. Através deste estudo de caso, pensa-se em possibilitar uma melhor compreensão de como é possível dentro de um território nacional surgir uma comunidade que cria sua própria estrutura abarcada por práticas culturais e econômicas características e por fim entender quais são seus efeitos no espaço geográfico
Keywords: Comunidade Visão Futuro; Comunidades alternativas; Geografia humana - Brasil; Comunidades cooperativas; Biologia economica; Porangaba (SP); Communal living; Human geography; Biology, Economic